(untitled) (Journal of School Administration Research and Development, 2023)
As a result of the COVID-19 pandemic, distance learning became popularized throughout the country as various schools were forced to transition to an online platform unexpectedly. This case study explored caregivers’ digital literacy self-efficacy and its connection to their academic involvement to primary grade students during distance learning in a public elementary school in the California’s Inland Empire. Data were collected through semi-structured interviews with open-ended questions conducted either in person or through Zoom. This study revealed that digital literacy self-efficacy of caregivers did not negatively affect the involvement they had in their students’ distance learning. There was also an increase in involvement no matter the computer comfortability of the caregiver and the challenges they faced throughout distance learning. The results of the study help inform district and school personnel on how to provide clear communication to caregivers and offer training for digital tools used throughout distance learning. Additionally, it guides districts on how taking the time to plan and create structure can provide caregivers a sense of comfortability knowing schools have a plan in place.